"Fire sales - what can be done about them?": On systemic risks in financial markets - Lucas Buchholz (Universität Witten/Herdecke, Fakultät für Wirtschaftswissenschaft, 2012)
In a world where wide parts of the real economy depend on the availability of capital, the question arises, of how such a system risk, endangering the welfare of millions of people could be controlled? Or how the negative effects of an ongoing fire sale could be reduced to a minimum? This essay tries to show different explanations for fire sales in the financial market and shows several possibilities, how fire sales could be dealt with. First it is going to give an introduction to fire sales, especially of financial assets, then presenting the different policy options. At the end, a conclusion will be drawn, trying to answer the question if fire sales which are extremely complex and depends on a million factors could be controlled by the government and what the implications of such a control might be. The essay is not looking at empirical data of fire sales but rather approaching the topic from an argumentative and theoretical point of view. The essay will also not cover the question if a single government would even be able to regulate the financial system to an extent that it would actually make a difference, or if a group of important governments, or even all major government would need to work together in order to be effective and make a real difference.
Keywords: 330